1998
DOI: 10.1046/j.1365-3083.1998.00435.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐4 and Interferon‐γ: The Quintessence of a Mutual Antagonistic Relationship

Abstract: The two cytokines interleukin (IL)-4 and interferon (IFN)-gamma play major roles in the generation and regulation of immune responses. Central in this respect is their mutually antagonistic functions. First, IL-4 promotes T helper cell type 2 (Th2) differentiation and stability and inhibits Th1-cell differentiation. A direct role of IFN-gamma in Th1-cell differentiation is debatable, whereas inhibition of Th2-cell differentiation and roles in Th1-cell stabilization are well established functions of IFN-gamma. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
134
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(141 citation statements)
references
References 94 publications
(94 reference statements)
4
134
1
Order By: Relevance
“…Induction of many giant cells by co-culture with BIL-2 suggested that IFN-γ had an important role in the inhibitory action, which was confirmed by the use of anti-IFN-γ neutralizing Ab (Figure 4). BIL-2 also expressed cytokines that are known to antagonize IFN-γ mediated activation of macrophage: IL-4, IL-13, 1L-10, and TGF-β (Gazzinelli et al, 1992;Hausmann et al, 1994;Paludan et al, 1997;Paludan et al, 1998). However, none of these could reverse IFN-γ mediated inhibition of osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Induction of many giant cells by co-culture with BIL-2 suggested that IFN-γ had an important role in the inhibitory action, which was confirmed by the use of anti-IFN-γ neutralizing Ab (Figure 4). BIL-2 also expressed cytokines that are known to antagonize IFN-γ mediated activation of macrophage: IL-4, IL-13, 1L-10, and TGF-β (Gazzinelli et al, 1992;Hausmann et al, 1994;Paludan et al, 1997;Paludan et al, 1998). However, none of these could reverse IFN-γ mediated inhibition of osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…BIL-2 express cytokines that are known to antagonize IFN-γ mediated activation of macrophage: IL-4, IL-13, IL-10, and TGF-β (Gazzinelli et al, 1992;Hausmann et al, 1994;Paludan et al, 1997;Paludan et al, 1998). We tested if these cytokines can antagonize the effect of IFN-γ on osteoclasts, too.…”
Section: Ifn -γ Is a Key Negative Regulator Of Osteoclast Differentiamentioning
confidence: 99%
“…5). IFN-g and IL-4 exert opposite effects on the regulation of immune responses, with IFN-g repressing IL-4 expression (16) and IL-4 antagonizing macrophage activities induced or enhanced by IFN-g (17). Activation of the Ras-mitogen-activated protein kinase pathway in T-helper type 2 cells has been shown to alter IL-4R function directly (18), although our data show a correspondence between the mutant k-ras expression signature and IL-4-induced genes (Fig.…”
Section: Responses Of A549 To Cytokine Treatments In Vitro Are Encodementioning
confidence: 99%
“…DUOX2 gene expression in the lungs has been responsive for the production of cytokine IFN-γ (Th1 pathway), while DUOX1 has been linked to the production of cytokine IL4 (Th2 pathway) (Harper et al, 2005). One interesting point is that a positive association between IFN-γ and IL4 expression was noted, despite the fact that these cytokines have been shown to have antagonistic functions (Paludan, 1998;Lees et al, 2011). Lees et al (2011) have linked the expression of host oxidants and antioxidants in response to the parasite infection, showing that IL4 appears to be strongly linked to a proliferation of immune cells, as well as to the induction or suppression of the two arms of the host oxidant and antioxidant response, respectively.…”
Section: Resultsmentioning
confidence: 99%